Implementasi Sertifikasi Fairtrade pada Kopi Gayo: Analisis Posisi Petani dalam Struktur Perdagangan Alternatif - Harri Fajri (Journal of World Trade Studies, 2015)
Fair Trade is an international movement trying to save farmers and workers in Global South from unfair practices of trade. In the globalized economy era this movement is getting bigger. However, the success of Fair Trade movement leads to grand debate since it depends on the involvement of corporations who are being avoided at the first time this movement began. This article discusses the implementation of Fair Trade on Gayo Coffee under Fairtrade certification scheme governed by Fairtrade Labeling Organization (FLO). It focuses on how FLO can transform farmer position in its commercial network. This article finds that certification scheme under FLO cannot guarantee farmer the best position in the international coffee chain. It argues that it is caused by the role of cooperation that is just dominated by few people instead farmers as a whole.